CD206 Expression in Induced Microglia-Like Cells From Peripheral Blood as a Surrogate Biomarker for the Specific Immune Microenvironment of Neurosurgical Diseases Including Glioma - Tanaka, Shunya; Ohgidani, Masahiro; Hata, Nobuhiro; Inamine, Shogo; Sagata, Noriaki; Shirouzu, Noritoshi; Mukae, Nobutaka; Suzuki, Satoshi O.; Hamasaki, Hideomi; Hatae, Ryusuke; Sangatsuda, Yuhei; Fujioka, Yutaka; et al. (Frontiers in Immunology, 2021)
Targeting the unique glioma immune microenvironment is a promising approach in developing breakthrough immunotherapy treatments. However, recent advances in immunotherapy, including the development of immune checkpoint inhibitors, have not improved the outcomes of patients with glioma. A way of monitoring biological activity of immune cells in neural tissues affected by glioma should be developed to address this lack of sensitivity to immunotherapy. Thus, in this study, we sought to examine the feasibility of non-invasive monitoring of glioma-associated microglia/macrophages (GAM) by utilizing our previously developed induced microglia-like (iMG) cells. Primary microglia (pMG) were isolated from surgically obtained brain tissues of 22 patients with neurological diseases. iMG cells were produced from monocytes extracted from the patients’ peripheral blood. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) revealed a significant correlation of the expression levels of representative markers for M1 and M2 microglia phenotypes between pMG and the corresponding iMG cells in each patient (Spearman’s correlation coefficient = 0.5225, P <0.0001). Synchronous upregulation of CD206 expression levels was observed in most patients with glioma (6/9, 66.7%) and almost all patients with glioblastoma (4/5, 80%). Therefore, iMG cells can be used as a minimally invasive tool for monitoring the disease-related immunological state of GAM in various brain diseases, including glioma. CD206 upregulation detected in iMG cells can be used as a surrogate biomarker of glioma.